2018
DOI: 10.3390/e20090655
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemical Fluctuations on Stacking Fault Energies of CrCoNi and CrMnFeCoNi High Entropy Alloys from First Principles

Abstract: Medium and high entropy alloys (MEAs and HEAs) based on 3d transition metals, such as face-centered cubic (fcc) CrCoNi and CrMnFeCoNi alloys, reveal remarkable mechanical properties. The stacking fault energy (SFE) is one of the key ingredients that controls the underlying deformation mechanism and hence the mechanical performance of materials. Previous experiments and simulations have therefore been devoted to determining the SFEs of various MEAs and HEAs. The impact of local chemical environment in the vicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 69 publications
1
38
0
Order By: Relevance
“…The SFEs of fcc austenitic steels, particularly of high-Mn steels, have empirically been known to correlate with their deformation behaviors [63][64][65][66][67]. Also for 3d-transitionelement-based HEAs, their SFEs have also been measured in experiments [8,17,26,[68][69][70][71] and computed based on firstprinciples simulations [72][73][74][75][76][77][78][79][80][81][82][83][84]. While the impact of C atoms on the SFEs of HEAs has also been discussed in experimental fcc hcp FIG.…”
Section: A Stacking-fault Energymentioning
confidence: 99%
See 1 more Smart Citation
“…The SFEs of fcc austenitic steels, particularly of high-Mn steels, have empirically been known to correlate with their deformation behaviors [63][64][65][66][67]. Also for 3d-transitionelement-based HEAs, their SFEs have also been measured in experiments [8,17,26,[68][69][70][71] and computed based on firstprinciples simulations [72][73][74][75][76][77][78][79][80][81][82][83][84]. While the impact of C atoms on the SFEs of HEAs has also been discussed in experimental fcc hcp FIG.…”
Section: A Stacking-fault Energymentioning
confidence: 99%
“…In first-principles simulations for 0 K, negative SFEs are rather common for 3d-transition-element-based HEAs [76][77][78][80][81][82]84,127,128]. Various factors such as lattice vibrations [12,78,81], magnetic fluctuations [12,73,127], chemical short-range order [82], and chemical fluctuations close to the stacking faults [83,128] are known to substantially modify the absolute value of the SFEs. In addition, a recent firstprinciples study found that a potential Cr sublattice ordering could further increase the SFE of CrCoNi [82].…”
Section: A Phase Stability and Sfe Of The Interstitial-free Crmnfeconimentioning
confidence: 99%
“…The advantage of this method is that it is possible to calculate several alloy compositions with less effort than the one required for an experimental determination of the same alloys. So far, the systems CoCrFeMnNi [9,10,13,14], AlCoCrCuFeNi, and AlCoCrFeNi [15] have been investigated regarding their SFE. A comprehensive list can be found in Reference [12].…”
mentioning
confidence: 99%
“…A comprehensive list can be found in Reference [12]. First-principle methods have even allowed the constructions of property maps, where the SFE can be read as a function of the chemical composition [14], which can be used to predict the expected physical acting mechanisms. The experimental determination of the SFE, although it is arguably more laborious, is as important as its computational calculation because, as accurate as they are, ab initio calculations still rely on a model, which may not be accurate for some conditions.…”
mentioning
confidence: 99%
“…Ab initio calculations have been successfully utilized to estimate the SFEs of various HEAs. To take the effect of magnetic ordering and VEC upon SFE into consideration, in the present study we further employ ab initio calculations to efficiently screen for quinary compositions based on the SFEs [1,30,[34][35][36][37][38][39][40][41] and design nonequiatomic HEAs with TRIP and/or TWIP. We first computationally screen for SFEs of alloys in the quasiternary Cr 20 Mn x Fe y Co 20 Ni z (x + y + z = 60, at.…”
mentioning
confidence: 99%